Age-dependent response of the human nasal epithelium to rhinovirus infection. Issue 5 (5th November 2020) - Usemann, Jakob; Alves, Marco P.; Ritz, Nicole; Latzin, Philipp; Müller, Loretta
Rhinovirus-induced wheezing in early childhood is a major risk factor for later asthma [1, 2] and rhinovirus infections have been identified as a main reason for asthma exacerbations [3–5]. While rhinovirus infections can manifest with a severe clinical course, rhinoviruses can also colonise the respiratory tract asymptomatically [6–8]. Thus, additional factors seem to determine which children develop a symptomatic rhinovirus infection and are at increased risk for asthma development, and which remain asymptomatic. For example, there is a genetic susceptibility, since rhinovirus-induced wheezing and specific genetic variants increase the risk for asthma [9]. After rhinovirus (RV) infection, RV viral loads are higher and immune factor expressions lower in nasal epithelial cells from children versus adults in vitro . This may explain age-dependent severity of RV infections and association with asthma development https://bit.ly/2zNfJhD